The Role of Digitalization, Agility, and Capability on Integration and Its Impact on Performance: A Study on the Retail Healthcare Supply Chain in Jakarta - Devina, Devina; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to examine the impact of digitalization in the supply chain on different elements of supply chain management. Based on the presented research and analysis, it can be concluded that supply chain digitalization positively impacts supply chain agility and capability. Furthermore, supply chain agility and capability have a positive impact on supply chain integration. Supply chain integration positively impacts supply chain performance. This study demonstrates that supply chain digitalization has a positive impact on supply chain performance by utilizing supply chain integration as a mediator. The study findings indicate that supply chain digitalization does not directly or significantly impact supply chain integration. These findings offer valuable insights into the impact of supply chain digitalization on overall performance through different mediation mechanisms. They also contribute to the advancement of theory and practice in supply chain management.